2016
DOI: 10.3758/s13414-016-1151-2
|View full text |Cite
|
Sign up to set email alerts
|

Stroking me softly: Body-related effects in effect-based action control

Abstract: Empirical investigations of ideomotor effect anticipations have mainly focused on action effects in the environment. By contrast, action effects that apply to the agent's body have rarely been put to the test in corresponding experimental paradigms. We present a series of experiments using the response-effect compatibility paradigm, in which we studied the impacts of to-be-produced tactile action effects on action selection, initiation, and execution. The results showed a robust and reliable impact if these ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 70 publications
4
33
0
Order By: Relevance
“…The aim of this study was to provide evidence for the role of tactile effects in the anticipation of actions while the ideomotor theory implies that the proximal information processed by proprioception is of less importance for the representation of actions (Osiurak and Badets 2014;Pfister and Kunde 2013). If it is well established that distal effects (i.e., visual or auditory) are important for anticipation of action (e.g., Elsner and Hommel 2001;Kunde 2001;Kunde et al 2004), few studies have shown a similar role for proximal effects (Pfister et al 2014;Wirth et al 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The aim of this study was to provide evidence for the role of tactile effects in the anticipation of actions while the ideomotor theory implies that the proximal information processed by proprioception is of less importance for the representation of actions (Osiurak and Badets 2014;Pfister and Kunde 2013). If it is well established that distal effects (i.e., visual or auditory) are important for anticipation of action (e.g., Elsner and Hommel 2001;Kunde 2001;Kunde et al 2004), few studies have shown a similar role for proximal effects (Pfister et al 2014;Wirth et al 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, based on Kunde's paradigm, Pfister et al (2014) and Wirth et al (2016) specifically explored proximal effects (see also ten Hoopen et al 1982). They used a response-effect compatibility paradigm where participants answer to a stimulus and responses were followed by a tactile effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because imitation and counterimitation affected participants' responses in Experiment 1, we concluded our experimental setup was not able to measure these effects. Since the movement of a single finger is not as distinct as a movement of the whole arm, we assumed that participants might not have paid sufficient attention to the movement of the hand (for a similar discussion, see Janczyk, Yamaguchi, Proctor, & Pfister, 2015;Müller, 2016;Wirth, Pfister, Brandes, & Kunde, 2016).…”
Section: Stimuli and Apparatusmentioning
confidence: 99%
“…The role of action effects for performance has been described by ideomotor theory (Hommel, Müsseler, Aschersleben, & Prinz, 2001;James, 1890;Shin, Proctor, & Capaldi, 2010), which assumes that humans produce actions by anticipating the intended sensory consequences of these actions. For instance, a key press in an experiment might be produced by anticipating the proprioceptive or visual consequences of this key press (Janczyk, Durst, & Ulrich, 2017;Janczyk & Lerche, 2018;Pfister & Kunde, 2013;Wirth, Pfister, Brandes, & Kunde, 2016). If motor actions can be selected using codes for their sensory consequences, it can reasonably be assumed that actors monitor the ultimately produced effects as well, to determine whether the intended consequences have actually been realized or to establish new action effect associations.…”
mentioning
confidence: 99%